Dekolorisasi Limbah Cair Batik Menggunakan Miselium Jamur yang Diisolasi dari Limbah Baglog Pleurotus ostreatus - Anna Yulita; Sri Lestari; Ratna Stia Dewi (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2013)
Batik industries have negative impacts on the environment from the dye used. An alternative method for decolorization in batik wastewater using the fungi Pleurotus ostreatus was grown in baglog. Spent mushroom (baglog) still contains fungal mycelium of P. ostreatus and contaminant fungus such as Penicillium sp., and Aspergillus sp.). Those fungi have a potential to decoloring dyes in batik wastewater. The aim of this research was to determine the ability of fungal mycelium isolated from spent mushroom P. ostreatus at decoloring batik wastewater, and determine the most effective fungal mycelium to decoloring batik wastewater. The results showed that the mycelium isolated from sewage baglog P. ostreatus was able to decoloring batik wastewater. Penicillium sp. mycelium is most effective at decoloring batik wastewater.